2016
DOI: 10.4037/ajcc2016317
|View full text |Cite
|
Sign up to set email alerts
|

Backrest Elevation and Tissue Interface Pressure by Anatomical Location During Mechanical Ventilation

Abstract: Background Backrest elevations less than 30° are recommended to reduce pressure ulcers, but positions greater than 30° are recommended during mechanical ventilation to reduce risk for ventilator-associated pneumonia. Interface pressure may vary with level of backrest elevation and anatomical location (eg, sacrum, heels). Objective To describe backrest elevation and anatomical location and intensity of skin pressure across the body in patients receiving mechanical ventilation. Methods In a longitudinal stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Since pressure is a primary mechanism in the formation of PrUls, higher backrest elevation positions used for VAP prevention may have deleterious effects on skin integrity (Linder-Ganzet al, 2008). Recently in the parent study for the present, secondary analysis, we found in critically ill, mechanically ventilated patients, that overall, mean tissue interface pressures were less in the scapula and heel than in trochanter and sacral area (Grap et al, 2016). We also found that inter-face pressure decreased as backrest elevation increased in the scapula, but not in the sacrum, heels or trochanter (Grap et al, 2016).…”
Section: Introductionmentioning
confidence: 72%
“…Since pressure is a primary mechanism in the formation of PrUls, higher backrest elevation positions used for VAP prevention may have deleterious effects on skin integrity (Linder-Ganzet al, 2008). Recently in the parent study for the present, secondary analysis, we found in critically ill, mechanically ventilated patients, that overall, mean tissue interface pressures were less in the scapula and heel than in trochanter and sacral area (Grap et al, 2016). We also found that inter-face pressure decreased as backrest elevation increased in the scapula, but not in the sacrum, heels or trochanter (Grap et al, 2016).…”
Section: Introductionmentioning
confidence: 72%
“…20 Subjects were enrolled in the study within 24 h of intubation, and sacral images were obtained daily for up to 7 days. Data were collected from February 2010 to May 2012.…”
Section: Sample and Settingmentioning
confidence: 99%
“…This secondary analysis of data from a larger study, 22 compared sacral HFUS tissue characteristics (dermal thickness and dermal density) with visual examination of the sacral HFUS image over multiple day-to-day comparisons, up through study day 7 for 113 critically ill subjects. We found no association among dermal density, dermal thickness and visual examination of changes in sacral HFUS images for any day-to-day comparison.…”
Section: Discussionmentioning
confidence: 99%
“…22 The study was approved by the university Institutional Review Board (IRB) and informed consent was obtained from the subject’s legally authorized representative (LAR). Because the parent study included use of a pressure mapping system that may enhance skin moisture, exclusion criteria included patients who had significant skin moisture risk as determined by the Braden scale of “constantly moist”.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation